A taxonomic review of the genus Frisilia Walker (Lepidoptera: Lecithoceridae), with description of two new species - Park, Kyu-Tek; Wu, Chunseng; Kun, Andras; Sohn, Jae-Cheon (Zootaxa, 2008)
The genus Frisilia Walker of the world is reviewed, with all of the 31 known species including two new species, F. cornualis sp. nov. and F. nesiotes sp. nov. The genus can be divided into the nesciatella and the anningensis species groups, on basis of the presence or absence of a median process of the juxta in the male genitalia. For all of the known species, we provide photos of adults and their male or female genitalia, all available taxonomic information including original references, type localities, type depositories, sources of available specimens, geographical distributions, and some recently collected data of the species. Frisilia striapunctata Wu is transferred to the genus Homaloxestis Meyrick, due to the normal slender labial palpus of the male and its wing venation. Frisilia drimyba Diakonoff (1967), known from the Philippines, is excluded from the genus Frisilia because of its lanceolate forewing with sharply pointed apex.